A retrospective evaluation of vertical bone loss around dental implants following immediate placement and immediate loading. - Muthray, Enesh (My University, 2013)
The immediate placement and loading of dental implants has many advantages and is an on-going focus of interest and research. Identifying factors that decrease vertical bone loss associated with implants might improve the prognosis of this protocol. This report evaluated survival (defined as the implant being present at the last review of the patient) and success (determined by the vertical bone loss around an implant) of immediately placed and loaded dental implants. Moreover, it set to determine whether site of placement and implant length had any influence on survival and vertical bone loss and thus have predictive value when immediately placing and loading a dental implant. The study was a retrospective clinical study consisting of a series of patients from an Oral and Maxillofacial surgeon’s private practice. Forty implants in 17 patients were analysed by comparing orthopantomographic radiographs taken immediately post placement and at the final review visit. Survival was determined for the sample and within the 2 parameters mentioned (i.e. implant length and placement site). Bone levels were measured on the radiographs of the subject concerned. Distortion and variance of the radiograph machine was calculated and all measurements corrected for distortion. The rate of bone loss and survival was determined for the sample. Success, or vertical bone loss, was judged by the rate of vertical bone loss measured for the entire sample and also within the two parameters. Four sites of placement were assessed, anterior maxilla, posterior maxilla, anterior mandible and posterior mandible. Two implant lengths were assessed, < 15mm and ≥ 15mm. The results were then analysed for significance to see if site of placement or length of implant influenced survival or vertical bone loss around the implant. There were no implant losses and therefore survival was 100%. The average rate of bone loss for the sample was 0.80mm per annum, which is within the internationally accepted norm of 1.5mm in the first year of placement. As survival was 100%, no statistical analysis was done for this parameter. There were statistically significant differences in the rate of bone loss with regards to the site that an implant was placed. The rate of loss was highest in the posterior maxilla, followed by the anterior mandible and then the posterior mandible. The anterior maxilla had the lowest rate of bone loss. Implant lengths of 15mm or longer had a statistically significant, higher rate of bone loss than implants shorter than 15mm. This study concludes that different implant sites have different success outcomes and that immediately placed and loaded implants, placed in the anterior maxilla, will be associated with less marginal bone loss. Similarly, with respect to implant length, implants shorter than 15mm enjoyed diminished bone loss. These results are expected in some aspects (i.e. survival and rate of bone loss of the sample as a whole), but are unusual in others (i.e. the rate of bone loss in the anterior maxilla being lower than traditionally more predictable sites, and rate of bone loss being less in shorter implants). It could be attributed to inherent difficulty in accurately assessing images in the anterior maxilla on an orthopantomographic radiograph, which would explain the results with respect to site of placement, or a number of flaws in the design of the study. These assumptions are made empirically, as no study I am aware of has specifically compared vertical bone loss within parameters of length and site.